Universal testing for hepatitis B and hepatitis C in the emergency department: a cost-effectiveness and budget impact analysis of two urban hospitals in the United Kingdom - Jack Williams; Peter Vickerman; Elizabeth Smout; Emma E. Page; Khine Phyu; Mark Aldersley; Gaia Nebbia; Sam Douthwaite; Laura Hunter; Murad Ruf; Alec Miners (Cost Effectiveness and Resource Allocation, 2022)
Abstract Background Numerous studies have shown the effectiveness of testing for hepatitis B (HBV) and hepatitis C (HCV) in emergency departments (ED), due to the elevated prevalence amongst attendees. The aim of this study was to conduct a cost-effectiveness analysis of universal opt-out HBV and HCV testing in EDs based on 2 long-term studies of the real-world effectiveness of testing in 2 large ED’s in the UK. Methods A Markov model was used to evaluate ED-based HBV and HCV testing versus no ED testing, in addition to current testing practice. The two EDs had a HBV HBsAg prevalence of 0.5–0.9% and an HCV RNA prevalence of 0.9–1.0%. The analysis was performed from a UK health service perspective, over a lifetime time horizon. Costs are reported in British pounds (GBP), and outcomes as quality adjusted life years (QALYs), with both discounted at 3.5% per year. Incremental cost-effectiveness ratios (ICER) are calculated as costs per QALY gained. A willingness-to-pay threshold of £20,000/QALY was used. The cost-effectiveness was estimated for both infections, in both ED’s. Results HBV and HCV testing were highly cost-effective in both settings, with ICERs ranging from £7,177 to £12,387 per QALY gained. In probabilistic analyses, HBV testing was 89–94% likely to be cost-effective at the threshold, while HCV testing was 94–100% likely to be cost-effective, across both settings. In deterministic sensitivity analyses, testing remained cost-effective in both locations at ≥ 0.25% HBsAg prevalence, and ≥ 0.49% HCV RNA prevalence. This is much lower than the prevalence observed in the two EDs included in this study. Conclusions HBV and HCV testing in urban EDs is highly cost-effective in the UK, and can be cost-effective at relatively low prevalence. These results should be reflected in UK and European hepatitis testing guidelines.